Differential gene expression changes in children with severe dengue virus infections. - Martijn D de Kruif; Tatty E Setiati; Albertus T A Mairuhu; Penelopie Koraka; Hella A Aberson; C Arnold Spek; Albert D M E Osterhaus; Pieter H Reitsma; Dees P M Brandjes; Augustinus Soemantri; Eric C M van Gorp (Public Library of Science (PLoS), 2008)
BACKGROUND: The host response to dengue virus infection is characterized by the production of numerous cytokines, but the overall picture appears to be complex. It has been suggested that a balance may be involved between protective and pathologic immune responses. This study aimed to define differential immune responses in association with clinical outcomes by gene expression profiling of a selected panel of inflammatory genes in whole blood samples from children with severe dengue infections. METHODOLOGY/PRINCIPAL FINDINGS: Whole blood mRNA from 56 Indonesian children with severe dengue virus infections was analyzed during early admission and at day -1, 0, 1, and 5-8 after defervescence. Levels were related to baseline levels collected at a 1-month follow-up visit. Processing of mRNA was performed in a single reaction by multiplex ligation-dependent probe amplification, measuring mRNA levels from genes encoding 36 inflammatory proteins and 14 Toll-like receptor (TLR)-associated molecules. The inflammatory gene profiles showed up-regulation during infection of eight genes, including IFNG and IL12A, which indicated an antiviral response. On the contrary, genes associated with the nuclear factor (NF)-kappaB pathway were down-regulated, including NFKB1, NFKB2, TNFR1, IL1B, IL8, and TNFA. Many of these NF-kappaB pathway-related genes, but not IFNG or IL12A, correlated with adverse clinical events such as development of pleural effusion and hemorrhagic manifestations. The TLR profile showed that TLRs were differentially activated during severe dengue infections: increased expression of TLR7 and TLR4R3 was found together with a decreased expression of TLR1, TLR2, TLR4R4, and TLR4 co-factor CD14. CONCLUSIONS/SIGNIFICANCE: These data show that different immunological pathways are differently expressed and associated with different clinical outcomes in children with severe dengue infections.